OPTIMIZATION OF ARTHROSPIRA PLATENSIS SUSPENSIONS: EVALUATING THE INFLUENCE OF SUSPENDING AGENT VARIATIONS ON PHYSICAL STABILITY (Proceedings OPTIMAL, 2026)
Arthrospira platensis is one of the microalgae rich in protein, vitamins, minerals, and antioxidants, making it a promising raw material for the formulation of pharmaceutical and nutraceutical products. This research aims to develop a suspension formulation from Arthrospira platensis powder that meets the physical properties of a suspension formulation and to determine a good formulation for Arthrospira platensis powder suspension by modifying the formulation regarding the concentration of the suspending agent used. The research methods include formulating suspensions using various types of materials and evaluating their physical stability (organoleptic properties), viscosity, pH, solution density, and sedimentation. Suspension preparations of Arthrospira platensis powder were made using 3 formulas with varying concentrations of CMC-Na as a suspending agent. The concentrations for each formula were: Formula I (0.25%), Formula II (0.5%), and Formula III (1%). Results: Based on the research and the results obtained, the viscosity values using spindle No. 2 and a speed of 20 were: Formula I 278.5 cp, Formula II 352 cp, and Formula III 401.5 cp. Therefore, the viscosity obtained for Formula II was better compared to Formula I and Formula III. The formulation of Arthrospira platensis powder suspension using CMC-Na as a suspending agent affects the viscosity of the preparation. The higher the concentration of CMC-Na used, the higher the viscosity of the suspension preparation